Coincidence study of core-ionized adamantane: site-sensitivity within a carbon cage?. Issue 47 (29th November 2022) - Ganguly, Smita; Gisselbrecht, Mathieu; Eng-Johnsson, Per; Feifel, Raimund; Hervieux, Paul-Antoine; Alfaytarouni, Zeinab; Fink, Reinhold F.; Díaz-Tendero, Sergio; Milosavljević, Aleksandar R.; Rousseau, Patrick; Maclot, Sylvain
Abstract : Can we observe site-sensitivity after X-ray core-ionisation of a symmetric molecule composed of the same heavy atom such as the carbon cage adamantane? We investigate this question using electron-ion coincidence spectroscopy and theoretical methods. Abstract : We investigate the fragmentation dynamics of adamantane dications produced after core-ionization at the carbon edge followed by Auger decay. The combination of high-resolution electron spectroscopy, energy-resolved electron-ion multi-coincidence spectroscopy and different theoretical models allows us to give a complete characterization of the processes involved after ionization. We show that energy- and site-sensitivity is observed even for a highly-symmetric molecule that lacks any unique atomic site.